2021
DOI: 10.3389/fnbeh.2020.612430
|View full text |Cite|
|
Sign up to set email alerts
|

Plasticity of Carbohydrate Transport at the Blood-Brain Barrier

Abstract: Neuronal function is highly energy demanding, requiring efficient transport of nutrients into the central nervous system (CNS). Simultaneously the brain must be protected from the influx of unwanted solutes. Most of the energy is supplied from dietary sugars, delivered from circulation via the blood-brain barrier (BBB). Therefore, selective transporters are required to shuttle metabolites into the nervous system where they can be utilized. The Drosophila BBB is formed by perineural and subperineurial glial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…The copyright holder for this preprint this version posted September 14, 2021. ; https://doi.org/10.1101/2021.09.13.460173 doi: bioRxiv preprint Genes involved in central glucose metabolism as well as insulin signaling are also candidate modifiers. MFS5 acts as a transporter of both glucose and trehalose for the uptake of these sugars from circulation (McMullen et al 2021). Glucose-6-phosphatase (G6P) is the last ratelimiting step in both gluconeogenesis and glycogenolysis, which are used to generate glucose for release into the body during fasting (Gaudet et al 2011;Lizák et al 2019).…”
Section: Analysis Of Candidate Modifiersmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 14, 2021. ; https://doi.org/10.1101/2021.09.13.460173 doi: bioRxiv preprint Genes involved in central glucose metabolism as well as insulin signaling are also candidate modifiers. MFS5 acts as a transporter of both glucose and trehalose for the uptake of these sugars from circulation (McMullen et al 2021). Glucose-6-phosphatase (G6P) is the last ratelimiting step in both gluconeogenesis and glycogenolysis, which are used to generate glucose for release into the body during fasting (Gaudet et al 2011;Lizák et al 2019).…”
Section: Analysis Of Candidate Modifiersmentioning
confidence: 99%
“…In addition, MFS3 and Pippin are involved in carbohydrate transport in the perineurial glia. Interestingly, MFS3 or Pippin null mutants are rescued via compensatory upregulation of Tret1-1, another bloodbrain barrier carbohydrate transporter, while RNAi-mediated knockdown of Mfs3 and pippin is not compensated for (McMullen et al, 2020). Trehalose is subsequently metabolically Biology Open • Accepted manuscript processed through glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila the blood-brain barrier is established by perineurial and subperineurial glial cells ( Stork et al, 2008 ). Perineurial cells express trehalose transporters and participate in maintaining the energy homeostasis of the brain ( McMullen et al, 2020 ; Volkenhoff et al, 2015 ). The subperineurial glial cells block paracellular diffusion by interdigitating cell–cell processes and the formation of septate junctions ( Babatz et al, 2018 ; Bundgaard and Abbott, 2008 ; Schwabe et al, 2005 ; Stork et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the MAN-modified liposome, the same as glucose, would be pumped out to bloodstream after entering CNS, thus preventing the concentration of chemotherapeutic agent in the brain because of the GLUT1 expressing on both the luminal and abluminal membranes on the endothelial cells of BBB. 19 This indicated that other ways are needed to enhance the ability to cross the BBB and increase drug concentration in the brain.…”
Section: Introductionmentioning
confidence: 99%